Life-threatening Development of Cardiac Tamponade in the Span of 24 Hours - Kishi, Patrick (Clin Pract Cases Emerg Med, 2019)
Cardiac tamponade is a medical emergency that requires immediate treatment. Caused by the development of fluid in the pericardial space, it can result in a severe decrease in cardiac output. When encountering patients with severe hypotension and tachycardia, emergency physicians must always consider the diagnosis of tamponade to facilitate prompt and effective treatment and stabilization. We report our experience with a patient who developed life-threatening cardiac tamponade within a span of less than 24 hours.